Karakteristik Fisik dan Organoleptik Mi Basah Dari Campuran Tepung Terigu dan Tepung Kentang (Solanum Tuberosum) Termodifikasi Heat Moisture Treatment - Dhiya Nailatul Masruroh (Fakultas Teknologi Pertanian, 2025)
Wet noodles are noodles that go through a boiling process so that the water content contained in them can reach 52%. Efforts to develop noodle products with the addition of modified potato flour aim to determine the physical and organoleptic characteristics of wet noodles with various variations of modified potato flour substitution with Heat Moisture Treatment (HMT), as well as to determine the best mixture formulation. The average value of physical characteristics is tensile strength (22.52×102Dyne/mm2 -32.29×102Dyne/mm2 ), rehydration strength (155.4436%-161.4860%), cooking loss (31.4320%-32.0804%), swelling strength (10.6944%-12.5%), L* color value (52.2-52.4), a* color value (6.3-6.7), and b* color value (17.5-17.6). The sensory attribute values of both treatments have quite high values including color (5.43-4.67), odor (5.08-5.28), texture (5.08-5.14), taste (4.47-5.57), and overall (4.85-5.65). Of the 7 formulations, there are 1 best formulation when compared to the control, namely treatment P1.
Reaploud Repository February 2026_Hasyim
Keywords: noodles; modified potato flour; heat moisture treatment